2017
DOI: 10.1175/jcli-d-16-0827.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Seasonal Cycles of Tropical Cyclone Potential Intensity

Abstract: Recent studies have investigated trends and interannual variability in the potential intensity (PI) of tropical cyclones (TCs), but relatively few have examined TC PI seasonality or its controlling factors. Potential intensity is a function of environmental conditions that influence thermodynamic atmosphere-ocean disequilibrium and the TC thermodynamic efficiency-primarily sea surface temperatures and the TC outflow temperatures-and therefore varies spatially across ocean basins with different ambient conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 58 publications
5
69
0
Order By: Relevance
“…This means that Tout is the warmest and OTL is the lowest in the NA among four basins (Figures c and d). These are consistent with the results in Gilford et al (), who found that OTL in the NA is lower than that in the WNP but is closer to that in the ENP, and correspondingly the outflow layer temperature in the NA is warmer than that in the WNP and ENP (see their Figure 2b). Gilford et al () also found that in the summer months when SSTs are the warmest, outflow temperatures are anomalously warm in the seasonal cycle in addition to being deeper into the stratosphere.…”
Section: Interbasin Differences In Environmental Atmospheric Factorssupporting
confidence: 93%
See 2 more Smart Citations
“…This means that Tout is the warmest and OTL is the lowest in the NA among four basins (Figures c and d). These are consistent with the results in Gilford et al (), who found that OTL in the NA is lower than that in the WNP but is closer to that in the ENP, and correspondingly the outflow layer temperature in the NA is warmer than that in the WNP and ENP (see their Figure 2b). Gilford et al () also found that in the summer months when SSTs are the warmest, outflow temperatures are anomalously warm in the seasonal cycle in addition to being deeper into the stratosphere.…”
Section: Interbasin Differences In Environmental Atmospheric Factorssupporting
confidence: 93%
“…These are consistent with the results in Gilford et al (), who found that OTL in the NA is lower than that in the WNP but is closer to that in the ENP, and correspondingly the outflow layer temperature in the NA is warmer than that in the WNP and ENP (see their Figure 2b). Gilford et al () also found that in the summer months when SSTs are the warmest, outflow temperatures are anomalously warm in the seasonal cycle in addition to being deeper into the stratosphere. Compared with both QPBL and SST‐T1000 (Figures a and b), overall Tout and OTL show larger variabilities at low SST than at high SST (Figures c and d) across all four basins, and are the largest in the WNP for SST below 29 °C.…”
Section: Interbasin Differences In Environmental Atmospheric Factorssupporting
confidence: 93%
See 1 more Smart Citation
“…This difference in seasonal anomalies between the two stations could be closely associated with the difference in topography (Trivandrum being a coastal station and Gadanki an inland station). Other investigators also observed very weak (~1 K) and unclear seasonal variation in temperature in the altitude region below TTL base except in the ABL at tropical stations (e.g., Gilford, Solomon, & Emanuel, ; Hashiguchi et al, ). While the T ′ in the bottom layer of TTL is highest during premonsoon season (~1 K) and lowest during postmonsoon season (<1 K), at Trivandrum, this region is cooler (by 0.5 to −1 K) during the October to February period (postmonsoon and winter seasons) and warmer (by~1.5 K) during March to September period (premonsoon and summer monsoon) at Gadanki.…”
Section: Resultsmentioning
confidence: 95%
“…These anomalies, quite significant in the upper layer of the TTL, decrease at higher altitudes and become minimal at ~25 km height. The seasonal anomalies reported at other tropical regions also showed large values above CPT with significant peak at ~18 .5 km, but large seasonal contrast is observed between winter and summer with a peak‐to‐peak difference of ~5–8 K (Gilford et al, ; Hashiguchi et al, ; Kim & Son, ; Yulaeva, Holton, & Wallace, ). These features above CPT could be explained by the relatively long radiative relaxation time scale in the region (Randel, Garcia, & Wu, ), tropical upwelling near the CPT (Boehm & Lee, ), and the annual cycle of large‐scale circulations in the troposphere and stratosphere and their associated processes (Yulaeva et al, ).…”
Section: Resultsmentioning
confidence: 95%